Effectiveness inactivation of trypsin inhibitor fron brazilian cultivarof beans (Phaseolus vulgaris L.) - Paiva, Kelli Cristina [UNESP]; Carvalho, Maria Regina Barbieri de [UNESP]; Pizauro Júnior, Joao Martins [UNESP] (My University, 2011)
The trypsin inhibitor, an antinutritional factor, which is abundant in dycotiledoneous and monocotyledoneous, is usually inactivated by heating treatment. The inﬂ uence of pressure-cooking (121°C and 141kPa) for 30 min on, trypsin inhibitors concentration and inhibitors reactivation from ten Brazilian beans varieties of Phaseolus vulgaris L. namely: IAPAR-14, IAC-Carioca, Rudá, Corrente, IAC-Aruã, IAPAR-16, IAPAR-57, IAC-Carioca Pyatã, Carioca, Aporé, were investigated. The inhibitors reactivation was evaluated in comparison with the activity of raw and pressure-cooking. For raw the in vitro protein digestibility mean values ranged from 40% (in Carioca cultivar) to 60% (in IAC-Aruã cultivar), showing an increase from 11% to 37% using the autoclaving at 121°C and 141kPa. Among ten cultivars studied the trypsin inhibitor activity varied from 36.18UTI.mg-1 for IAC-Aruã to 63.33UTI.mg-1 for IAPAR-16. Trypsin inhibitor activity was totally inactivated by pressure-cooking. The study of the trypsin inhibitors reactivation using double-digestive pepsin-pancreatin enzymes in vitro showed a recovering activity from 34% up to 100%. Native inhibitor is resistant to double- digestive pepsin-pancreatin proteolysis, whereas autoclaving to 121oC.30 min-1 results in a non-native conformation that is susceptible to proteolysis, improving the digestibility and inactivate differentially the activity of trypsin inhibitors. The results of the thermal treatment of the beans show inactivation of the inhibitors, which may be due to formation of high molecular weight aggregates with other substances of the grain. The pepsin-pancreatin digestion of the inactivated inhibitor restores the activity, probably due to its retention by the digested fragments.
Eﬁcácia da inativação do inibidor de tripsina em cultivares brasileiras de feijão (Phaseolus vulgaris L.)
Keywords: Antinutritional factor; Heat treatment; In vitro protein digestibility; Inhibitor reactivation